IKEA: Enhancing Customer Experience through Digital Transformation - Mega Fitri Yani; Cindy Muhdiantini; Fitri Adini Firdaus; Hasan Abdullah Muhammad (STKIP PGRI Tulungagung, 2025)
Digital transformation has become a key driver for companies to remain relevant and competitive. IKEA, as one of the world's largest furniture retailers, has proactively embraced digital transformation as a core strategy to enhance customer experience. This research explores various digital initiatives by IKEA, including the development of the IKEA Place app using Augmented Reality (AR) technology and the enhancement of online platforms with advanced features. Additionally, IKEA has made strategic investments in digital technology in physical stores, such as interactive digital kiosks and mobile payment systems. This study utilizes a comprehensive literature review method, leveraging Google Scholar, Scopus, and company reports to ensure credible and up-to-date information. The findings indicate that IKEA's digital transformation has positively impacted customer satisfaction and loyalty. However, IKEA also faces various challenges in this transformation process. This research provides in-depth insights into IKEA's digital transformation journey, sustainability factors, Five Forces analysis, new business strategies, and recommendations for the future. In conclusion, IKEA's digital transformation has successfully significantly enhanced customer experience, albeit requiring ongoing adaptation and innovation.